A educação rural brasileira : limites e possibilidades do processo de nucleação em Patos de Minas, MG (1990-2002) - Sales, Suze da Silva (2007)
The present paper has the intention to make a historicity of the public politics concerning to the rural education in Brazil, and in especial in the city of Patos de Minas MG, being based on the comprehension of the economic, politic and social context that was being constructed in the Brazilian rural sector during the twentieth century. Having in mind that the new politics destined for the rural education are introduced through conservative management strategies and introduction of resources, the paper intends to identify the mainly actions developed in the Brazilian scenery, about the question of rural education, since its first initiatives to the most recent directed to the nucleation process. In this sense, we also show the Brazil History episodes that were important to understand the agrarian questions and helped that the status quo stayed in the field, where we can see inequality in the income distribution and in the work and production conditions. Going ahead, the text analyses the rural workers organization, in the beginning of the years 1980, as a time period to the researches that aim to study the rural context and its aspects, showing the thematic points that have a relation to the education, showing some reflections about the initiatives of the State and the civil society which tries to improve the teaching destined to the rural workers in Brazil. Following, the work intends to show the ways of the public politics destined to the rural areas in the city of Patos de Minas-MG, in the period of 1990 to 2002, moment that some actions were developed to introduce the nucleation in the rural areas of Patos de Minas, considering that this fact provoked structural transformations, that brought innovation, but were developed without the active participation of the rural workers or of the representative segments of them, like the rural workers and producers trade union, saving some interests and prejudicing others. It is necessary to rebuild this way to understand why the rural school does not carry out a more significant role in the emancipation of the rural worker.